Rickettsial Infections: A Clinician#x2019;s Diagnostic Dilemma (Global Journal of Medical Research, 2020)
Rickettsial diseases are arthropod borne zoonotic infections that are being increasingly recognized as one of the causes of pyrexia of unknown origin (PUO). These pathogens are gram-negative bacteria causing fever and rash, usually transmitted to humans by tick or flea bite. These infections must be differentiated from other febrile illnesses such as enteric fever, malaria, dengue, leptospirosis, and infectious mononucleosis. The common clinical presentation includes fever with chills and rigor, headache, vomiting, cough, conjunctival congestion and eschar. Presenting with varied and non-specific symptoms, ignorance, and low index of suspicion, they are often under-diagnosed due to the unavailability of the reliable diagnostic test. Weil- Felix test (WFT) is a non-specific heterophile tube agglutination test in which antibodies against rickettsiae are detected. If timely treatment with doxycycline is instituted the adverse consequences can be well averted.
Keywords: rickettsia; rash; fever; weil-felix test